Analisis Kesulitan Guru Biologi SMA Negeri 10 Bone Dalam Penerapan Kurikulum 2013 Di Masa Pandemi Covid-19 - Sitti Asmah; Romi Adiansyah; Nurmi Nurmi (Departement of Mathematics Education, 2023)
This study aims to determine the Difficulties of Biology Teachers of SMA Negeri 10 Bone in Implementing the 2013 Curriculum During the Covid 19 Pandemic. The type of research used is Qualitative descriptive research. This research focused on the difficulties of biology teachers of public Hight School 10 Bone in implementing the 2013 curriculum during the Covid 19 pandemic The sources of data in this study are, Interview guidelines, Documentation. The data collection techniques used are Recording, Listening, Analyzing and Documentation techniques. This study concluded that the factor that affects teacher difficulties in learning is that biology teachers have not mastered the use of the latest applications such as Google Classroom and others so they only use Whatsapp groups. While from the students themselves, there are still many who do not have online learning facilities such as android phones or data packages (this can be called an economic factor) and also limited signals